Pengembangan Aplikasi Multimedia Pembelajaran CD Tutorial Pada Mata Kuliah Berbasis Praktik - Rizqi Abdillah; Sunardi Sunardi; Deny Tri Ardianto (Teknodika, 2018)
The purpose of this research is to describe the needs of students to the application of CD tutotial as learning media at the course based on practice, its developing and the students’ responds towards the media used in the instructional process.  The program of Educational Technology is famous of its students who have a high capability in multimedia field of study as some of the courses relate to technology-based learning. Unfortunatelly, there are some obstacles coming up as the practice-based course has less optimum on its real class. It makes the researcher trying to develop an application of learning media in term of CD Tutorial to be applied at the class by the practice-based course. This research uses ADDIE developing model (Analysis, Design, Development, Implementation, Evaluation). The result of this research and development will be in term of media product which is later on will be done some evaluation tests from the expert teams, and at last filed test to know its effectiveness of its media on the instructional process.